Javanese Marriage Prohibitions from The Perspective of Social Construction Theory - M. Fathan Nur Rafi’; Agus Purnomo; Abid Rohmanu (Institut Agama Islam Negeri Ponorogo, 2026)
Background/Introduction: Marriage practices based on Javanese customs are still widely found in Pupus Village, Lembeyan District, Magetan Regency. One enduring tradition is the prohibition of certain marriages, which continues to be strongly believed by the community. Research Objectives: This study aims to examine the level of community belief in marriage prohibitions within Javanese customs and to analyze the underlying social construction. Methodology: This research employs a descriptive qualitative field approach. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Results: The findings indicate that community belief is influenced by the tradition of ilmu titen, which has been passed down through generations. The social construction is formed through three stages: externalization (adjustment to cultural values), objectification (acceptance as a collective heritage), and internalization (the absorption of values into individuals). Differences in education level and religious understanding also affect the degree of belief. Unique Contribution: This study contributes to socio-cultural studies by applying social construction theory to explain the persistence of marriage prohibitions in a rural Javanese context. Conclusion: Marriage prohibitions persist due to strong social construction embedded in community life. Recommendations: Efforts are needed to promote contextual religious and cultural education and to encourage further research integrating local traditions with contemporary perspectives.